Piagam ASEAN, Legalitas Tonggak Baru, Menuju Integrasi Regional - Djafar, Zainuddin (UI Scholars Hub, 2009)
The ASEAN Charter which was ratified on December 15, 2008 has drawn various reactions from The regional community. This writing seeks to evaluate upon what are the Charter’s strength and weakness. The Charter is indeed not a tool which can directly solve the regional problems, yet at least now Southeast Asiab owns its set of mechanism which shall bind its members legally and can be used to create regionally formal rules. The Issues and challenges which the Carter seeks to solve includes: democratization, human rights and the ASEAN single market of 2015. The diversifying socio cultural aspects as well as other issues remain as challenges in creating a common perception and recommendation for the three issues. Therefore, despite of its ratification, the ASEAN Charter must undertake a difficult test.